Discovering what our players will thank us for. (Data Science Salon, 2020)
"The gaming industry, and the entertainment industry as a whole, is a relentless battle for the human attention span. From acquiring the 'right' audience to providing the 'right' content, a game's success hinges on identifying what is "right" better than your competition. Applying proper research techniques, identifying opportunities within this research, and devising smarter delivery systems to users require constant evolution in technology and methodology. In this talk, [the presenter] will discuss how Zynga's data science team has risen to this challenge, incorporating interdisciplinary techniques to fit the needs of our live-game operations."--Resource description page